2022
DOI: 10.1111/cid.13062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of smoking on peri‐implant bleeding on probing

Abstract: Background Studies around natural dentition demonstrated that smoking can reduce the tendency of inflamed tissue to bleed upon probing after controlling for possible confounders. In addition, previous research suggested that smokers may present alterations of the peri‐implant microbiome. Aim This study aimed at investigating the impact of smoking on: (1) peri‐implant bleeding on probing (BOP; primary objective); (2) the association between BOP/bone loss and BOP/visible gingival inflammation; (3) peri‐implant m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…[29][30][31] The present study excluded smoking and former smoking participants, as this is considered a risk factor for successful implant treatment. 32,33 Thin biotype extraction sites were not included, as they were reported to demonstrate a three times higher risk of mid-facial recession and may require soft-tissue augmentation along with implant placement, 34 which would confound the effect of surgical technique and is out of the current trial's scope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[29][30][31] The present study excluded smoking and former smoking participants, as this is considered a risk factor for successful implant treatment. 32,33 Thin biotype extraction sites were not included, as they were reported to demonstrate a three times higher risk of mid-facial recession and may require soft-tissue augmentation along with implant placement, 34 which would confound the effect of surgical technique and is out of the current trial's scope.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture of autogenous and xenogeneic bone combined the benefits of both types, as the former has an osteogenic effect with rapid remodeling, while the latter is slowly resorbing and hence provides a stable matrix over a longer period 29–31 . The present study excluded smoking and former smoking participants, as this is considered a risk factor for successful implant treatment 32,33 . Thin biotype extraction sites were not included, as they were reported to demonstrate a three times higher risk of mid‐facial recession and may require soft‐tissue augmentation along with implant placement, 34 which would confound the effect of surgical technique and is out of the current trial's scope.…”
Section: Discussionmentioning
confidence: 99%
“…The study thus concluded that the transition from health to mucositis and progression to peri-implantitis takes an alternate pathway in smokers, which includes the further enrichment of the microbiome and a decrease in diversity [ 92 ]. Another cross-sectional study compared the peri-implant microbiota in smokers and nonsmokers and also demonstrated a significantly higher microbial richness in smoker patients around implants affected by peri-implantitis as compared to either healthy implants or implants presenting with mucositis [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…In non-periodontitis subjects, 75% of individuals can share a core microbiome in the healthy peri-implant sulcus in smokers and nonsmokers, with smokers presenting with a more disease-associated core microbiome including a lower bacterial diversity [ 14 , 91 ]. The transition from health to peri-implant mucositis and progression to peri-implantitis in smokers includes further enrichment of the microbiome and a decrease in bacterial diversity [ 92 , 93 ]. In contrast, the shift from health to peri-implant mucositis in nonsmoker patients comprises a significant increase in bacterial diversity [ 92 ].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is known to affect the composition and metabolism of the oral microbiome and is considered a major risk factor for periimplantitis or periodontitis (Bizzarro et al, 2013;Moon et al, 2015;Tsigarida et al, 2015;Duan et al, 2017;Pimentel et al, 2018;Torrungruang et al, 2020;Amerio et al, 2022). Our results are consistent with previous studies, showing that even for a clinically healthy peri-implant environment, smoking increases the abundances of putative pathogens such as A. geminatus, E. saphenum, and P. denticola (Abusleme et al, 2013;Bao et al, 2017;Al Kawas et al, 2021) and regulates the functional potential of the peri-implant microbiome (Figure 1), shifting it to a more disease-related, sub-healthy status (Tsigarida et al, 2015).…”
Section: Discussionmentioning
confidence: 99%